Modeling Support and Resistance Zones in Financial Time Series with Stochastic and Volume-Weighted Methods; Contemporary Mathematics; Vol. 6, iss. 6 - Martyushev N. V. Nikita Vladimirovich; Spitsin V. V. Vladislav Vladimirovich; Khayrov M. A. Mark Albertovich; Spitsina (Spitsyna) L. Yu. Lubov Yurievna (2025, 2025)
Title screen